The effect of horizontally- or vertically directed plyometric bounding exercises on sprinting and jumping performance - Thomasian, B. C.; Chapman, D. W.; Blazevich, A. J. (Journal of Australian Strength and Conditioning, 2019)
Training interventions consisting of either horizontally- or vertically directed plyometric exercises may be implemented for the purpose of improving sprinting and vertical jumping performance.